Responses and strategies of Indonesian higher education during COVID-19 pandemic - Yusnaini Yusnaini; Eva Lydia; Mulyanto Mulyanto; Harry Yogsunandar; Anang Dwi Santoso (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study aimed to identify the responses and strategies of higher education in Indonesia in dealing with coronavirus disease 2019 (COVID-19). The data in this study came from several legal frameworks and news issued by relevant ministries as well as regulations and news released by universities which were analyzed to map how universities adapt to the COVID-19 situation. In addition, interview to faculty members, students and administrative staffs were also conducted. This study found that the relevant ministries responded no faster than the responses made by universities. The ministry has provided a series of regulations and also guidelines but unfortunately, the universities have published these things first. This research is an initial study to identify responses, obstacles to providing education, and research and community service in the COVID-19 era. This research is the first to investigate how universities conduct the three main tasks of the university in Indonesia investigating responses at the organizational and individual levels to identify responses and obstacles they find.